2020
DOI: 10.1007/s10899-020-09964-z
|View full text |Cite
|
Sign up to set email alerts
|

Online Problem Gambling: A Comparison of Casino Players and Sports Bettors via Predictive Modeling Using Behavioral Tracking Data

Abstract: In this study, the differences in behavior between two groups of online gamblers were investigated. The first group comprised individuals who played casino games, and the second group comprised those who bet on sports events. The focal point of the study was on problem gambling, and the objective was to identify and quantify both common and distinct traits that are characteristic to casino and sports problem gamblers. To this end, a set of gamblers from the gaming operator LeoVegas was studied. Each gambler wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
(40 reference statements)
1
16
1
1
Order By: Relevance
“…To what extent transitioning from online betting to casino playing, provoked by the COVID-19 situation, leads to long-term effects on prevalence of problem gambling ( 16 18 ) remains unknown and is an important topic for future research. Previous research shows that least amongst users of online gambling providers that offer both betting and casino games (as in the current study), there is likely to already be a great overlap such that a large proportion engage in both gambling types ( 21 , 32 ), suggesting that most players who transitioned during the COVID-19 outbreak simply changed their proportion of betting vs. casino gambling. Importantly, our data does not allow us to distinguish between activity from transitions between gambling modalities amongst existing gamblers, from that of new gamblers who may have turned to gambling due to pandemic-related anxiety or boredom ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 64%
“…To what extent transitioning from online betting to casino playing, provoked by the COVID-19 situation, leads to long-term effects on prevalence of problem gambling ( 16 18 ) remains unknown and is an important topic for future research. Previous research shows that least amongst users of online gambling providers that offer both betting and casino games (as in the current study), there is likely to already be a great overlap such that a large proportion engage in both gambling types ( 21 , 32 ), suggesting that most players who transitioned during the COVID-19 outbreak simply changed their proportion of betting vs. casino gambling. Importantly, our data does not allow us to distinguish between activity from transitions between gambling modalities amongst existing gamblers, from that of new gamblers who may have turned to gambling due to pandemic-related anxiety or boredom ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 64%
“…e famous Chinese academician Zhong Nanshan recommends that everyone exercise regularly [11][12][13]. In an environment where people across the country are healthy, using Internet+ sports to further promote and popularize sports.…”
Section: Analysis Of the Advantages Of Internet+ Sports In Urbanmentioning
confidence: 99%
“…Chagas and Gomes ( 2017 ) reported that initial studies on lottery tracking data relied on the same database ( Bwin ) and later ones were limited to a few databases and focused on very narrow time frames such as account opening or closing. More recently, additional gambling operators (e. g., ComeOn Group, Íslensk Getspá, Kindred, Leo Vegas, Norsk Tipping, Svenska Spel and win2day ) have made their databases available for researchers to study gambling behavior (Auer & Griffiths, 2013 , 2016 , 2017 , 2018 , 2020 Auer et al, 2018 , 2019a , 2019b , 2020 ; Fiedler, 2011 , 2013 ; Gainsbury et al, 2012 ; Gray et al, 2015 ; Ukhov et al, 2021 ). These studies cover different forms of gambling and only a few include lottery gambling (e.g., Auer & Griffiths, 2013 , 2014 , 2016 ; Auer et al, 2018 ; Gray et al, 2015 ) and none of these studies used a player/consumer segmentation method, such as the one we used in the present study, for the study of lottery gambling or even studied the population of a southern European country.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%